Intergenerational Online Health Information Searching and Brokering: Framing Health Literacy as a Family Asset. Issue 4 (21st March 2022) - Gonzalez, Carmen; Bollinger, Beth; Yip, Jason; Pina, Laura; Roldan, Wendy; Nieto Ruiz, Carolina
ABSTRACT: Latino populations are disproportionately impacted by health disparities and face both connectivity and health literacy challenges. As evidenced by the current global pandemic, access to reliable online health-related information and the ability to apply that information is critical to achieving health equity. Through a qualitative study on how Latino families collaborate to access online health resources, this work frames health literacy as a family-level mechanism. Interviews with parent-child dyads combined with online search tasks reveal how families integrate their individual skillsets to obtain, process, and understand online information about illnesses, symptoms, and even medical diagnoses. As they engage in intergenerational online health information searching and brokering, families creatively navigate information and communication technologies (ICTs) to address a range of health needs. Bilingual children help immigrant parents obtain urgent and non-urgent health information needed to care for other family members. When children are tasked with addressing a health need critical to their parent's wellbeing, they collaborate with their parents to obtain, interpret, and apply online health information. Intergenerational online health information searching and brokering thus reveals family-level strengths that can be leveraged to promote both health and digital literacy among marginalized populations.